Looking at export tariffs and export restrictions: The case of Argentina - Piñeiro, Valeria; Laborde Debucquet, David; Díaz-Bonilla, Eugenio; Elverdin, Pablo (2017)
Export taxes have been used in many countries. They have multiple effects at the macroeconomic and sectoral levels, including on the terms of trade (resulting from the market power of key suppliers), the reduction and stabilization of consumer prices (which influence food security) or on intermediate input prices (which may affect in different ways the processed goods using them), government revenues and income distribution. These taxes can also create serious negative externalities for trade partners and affect long-term investment and innovations in the targeted sectors. Recent years have been marked by a renewal of interest in this issue from the trade community. The 2007–08 food price crisis shed light on export policies’ dangerous consequences for food security during periods of price spikes (Anderson and Martin, 2011; Bouët and Laborde, 2011).